Analysis of the Function and Role of the DPRD as the Mandate of the People Viewed From the Perspective of Legal Philosophy - Wieke Dewi Suryandari; Sa’diyanto Sa’diyanto (Journal Research of Social Science, Economics, and Management, 2023)
Local government has a dual function of holding executive and legislative powers. Meanwhile, the DPRD acts as a managing or controlling institution which can approve certain changes or reject them altogether. However, the DPRD may occasionally submit proposals on its initiative regarding draft regional regulations. This study uses a qualitative approach, namely the approach used by researchers based on data stated by respondents orally or in writing, governing it by the legal hierarchy in Indonesia. Whereas the DPR/DPRD as people's representative institutions and functioning as legislators should form a law that does not deviate from the purpose of the law, namely to provide certainty to the community, justice to the community, and benefits to the community. In this case, the law is a tool to regulate the social balance, and the interests of society to realize the ideals of society. The formation of laws and regulations must also pay attention to the Theory and Objectives of Legal Politics, namely the policies of state administrators in the field of law that have been in effect, are in force, and will be in effect, sourced from the values prevailing in society to achieve the aspired goals of the state.